5.2.58 Problems 5701 to 5793

Table 5.283: Second order linear ODE

#

ODE

Mathematica

Maple

19458

\[ {}x^{2} y^{\prime \prime }-2 n x y^{\prime }+\left (a^{2} x^{2}+n^{2}+n \right ) y = 0 \]

19459

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-3\right ) y = {\mathrm e}^{x^{2}} \]

19460

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

19461

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+\frac {a^{2} y}{x^{4}} = 0 \]

19462

\[ {}\left (x^{3}-x \right ) y^{\prime \prime }+y^{\prime }+n^{2} x^{3} y = 0 \]

19463

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+m^{2} y = 0 \]

19464

\[ {}y^{\prime \prime }-\cot \left (x \right ) y^{\prime }-\sin \left (x \right )^{2} y = 0 \]

19465

\[ {}\sin \left (x \right )^{2} y^{\prime \prime }+\sin \left (x \right ) \cos \left (x \right ) y^{\prime }+y = 0 \]

19466

\[ {}\left (x^{2}+1\right )^{2} y^{\prime \prime }+2 x \left (x^{2}+1\right ) y^{\prime }+4 y = 0 \]

19467

\[ {}y^{\prime \prime }+\left (\tan \left (x \right )-1\right )^{2} y^{\prime }-n \left (n -1\right ) y \sec \left (x \right )^{4} = 0 \]

19468

\[ {}y^{\prime \prime }+\left (3 \sin \left (x \right )-\cot \left (x \right )\right ) y^{\prime }+2 \sin \left (x \right )^{2} y = 0 \]

19469

\[ {}3 x^{2} y^{\prime \prime }+\left (-6 x^{2}+2\right ) y^{\prime }-4 y = 0 \]

19470

\[ {}x y^{\prime \prime }+\left (x -2\right ) y^{\prime }-2 y = x^{2} \]

19471

\[ {}x^{2} y^{\prime \prime }+y^{\prime }-\left (x^{2}+1\right ) y = {\mathrm e}^{-x} \]

19472

\[ {}\left (x +2\right ) y^{\prime \prime }-\left (5+2 x \right ) y^{\prime }+2 y = \left (1+x \right ) {\mathrm e}^{x} \]

19473

\[ {}y^{\prime \prime }+y = x \]

19474

\[ {}y^{\prime \prime }+y = \csc \left (x \right ) \]

19475

\[ {}y^{\prime \prime }+4 y = 4 \tan \left (2 x \right ) \]

19476

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = \left (1-x \right )^{2} \]

19477

\[ {}y^{\prime \prime }-y = \frac {2}{1+{\mathrm e}^{x}} \]

19478

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-4 x y^{\prime }-\left (x^{2}+1\right ) y = x \]

19479

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = -4 x^{3} \]

19480

\[ {}x y^{\prime }-y = \left (x -1\right ) \left (y^{\prime \prime }-x +1\right ) \]

19482

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = x^{3} \]

19483

\[ {}\left (x^{2}+a \right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

19484

\[ {}y^{\prime \prime }-\frac {2 y^{\prime }}{x}+\left (n^{2}+\frac {2}{x^{2}}\right ) y = 0 \]

19485

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = x^{3}+3 x \]

19486

\[ {}\left (a^{2}-x^{2}\right ) y^{\prime \prime }-\frac {a^{2} y^{\prime }}{x}+\frac {x^{2} y}{a} = 0 \]

19487

\[ {}x^{4} y^{\prime \prime }+2 x^{3} y^{\prime }+n^{2} y = 0 \]

19488

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+\frac {a^{2} y}{-x^{2}+1} = 0 \]

19489

\[ {}\left (2 x -1\right ) y^{\prime \prime }-2 y^{\prime }+\left (3-2 x \right ) y = 2 \,{\mathrm e}^{x} \]

19490

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 8 x^{3} \]

19491

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+5\right ) y = x \,{\mathrm e}^{-\frac {x^{2}}{2}} \]

19492

\[ {}x \left (-x^{2}+1\right )^{2} y^{\prime \prime }+\left (-x^{2}+1\right ) \left (3 x^{2}+1\right ) y^{\prime }+4 x \left (x^{2}+1\right ) y = 0 \]

19493

\[ {}y^{\prime \prime }+\left (1-\frac {2}{x^{2}}\right ) y = x^{2} \]

19494

\[ {}\left (x^{3}-2 x^{2}\right ) y^{\prime \prime }+2 x^{2} y^{\prime }-12 \left (x -2\right ) y = 0 \]

19495

\[ {}x y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+\left (x +2\right ) y = \left (x -2\right ) {\mathrm e}^{2 x} \]

19496

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

19497

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

19498

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }-a^{2} y = 0 \]

19499

\[ {}x y^{\prime \prime } \left (x \cos \left (x \right )-2 \sin \left (x \right )\right )+\left (x^{2}+2\right ) y^{\prime } \sin \left (x \right )-2 \left (x \sin \left (x \right )+\cos \left (x \right )\right ) y = 0 \]

19500

\[ {}x y^{\prime \prime }-y^{\prime }+4 x^{3} y = x^{5} \]

19501

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-\left (4 x^{2}-3 x -5\right ) y^{\prime }+\left (4 x^{2}-6 x -5\right ) y = {\mathrm e}^{2 x} \]

19502

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+x y^{\prime } = m^{2} y \]

19503

\[ {}y^{\prime \prime }+\left (1-\frac {1}{x}\right ) y^{\prime }+4 x^{2} y \,{\mathrm e}^{-2 x} = 4 \left (x^{3}+x^{2}\right ) {\mathrm e}^{-3 x} \]

19504

\[ {}x y^{\prime \prime }+\left (x^{2}+1\right ) y^{\prime }+2 x y = 2 x \]

19505

\[ {}\left (x +2\right ) y^{\prime \prime }-\left (5+2 x \right ) y^{\prime }+2 y = \left (1+x \right ) {\mathrm e}^{x} \]

19506

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }-y = x \left (-x^{2}+1\right )^{{3}/{2}} \]

19507

\[ {}x^{2} y^{\prime \prime }-\left (x^{2}+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

19529

\[ {}2 y^{\prime \prime }+9 y^{\prime }-18 y = 0 \]

19533

\[ {}y^{\prime \prime }+n^{2} y = \sec \left (n x \right ) \]

19535

\[ {}y^{\prime \prime }-4 y^{\prime }+y = a \cos \left (2 x \right ) \]

19538

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \sin \left (x \right ) \]

19540

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x^{2} {\mathrm e}^{3 x} \]

19541

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = 2 \sinh \left (2 x \right ) \]

19542

\[ {}y^{\prime \prime }+a^{2} y = \cos \left (a x \right ) \]

19543

\[ {}y^{\prime \prime }-2 y^{\prime }+y = x \sin \left (x \right ) \]

19579

\[ {}x^{2} y^{\prime \prime }-2 y = x^{2}+\frac {1}{x} \]

19583

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 2 x^{2} \]

19585

\[ {}x^{2} y^{\prime \prime }+3 x y^{\prime }+y = \frac {1}{\left (1-x \right )^{2}} \]

19587

\[ {}\left (x +a \right )^{2} y^{\prime \prime }-4 \left (x +a \right ) y^{\prime }+6 y = x \]

19589

\[ {}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 4 \cos \left (\ln \left (1+x \right )\right ) \]

19591

\[ {}x^{2} y^{\prime \prime }-\left (2 m -1\right ) x y^{\prime }+\left (m^{2}+n^{2}\right ) y = n^{2} x^{m} \ln \left (x \right ) \]

19592

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+y = \frac {\ln \left (x \right ) \sin \left (\ln \left (x \right )\right )+1}{x} \]

19596

\[ {}\sqrt {x}\, y^{\prime \prime }+2 x y^{\prime }+3 y = x \]

19597

\[ {}2 x^{2} \left (1+x \right ) y^{\prime \prime }+x \left (7 x +3\right ) y^{\prime }-3 y = x^{2} \]

19603

\[ {}y^{\prime \prime } = x^{2} \sin \left (x \right ) \]

19604

\[ {}y^{\prime \prime } = \sec \left (x \right )^{2} \]

19610

\[ {}x y^{\prime \prime }+y^{\prime } = 0 \]

19614

\[ {}x y^{\prime \prime }-\left (2 x -1\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

19615

\[ {}\sin \left (x \right )^{2} y^{\prime \prime } = 2 y \]

19616

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }+x y^{\prime }-y = x \left (-x^{2}+1\right )^{{3}/{2}} \]

19617

\[ {}\left (x +2\right ) y^{\prime \prime }-\left (5+2 x \right ) y^{\prime }+2 y = \left (1+x \right ) {\mathrm e}^{x} \]

19618

\[ {}y^{\prime \prime }-\cot \left (x \right ) y^{\prime }-\left (1-\cot \left (x \right )\right ) y = {\mathrm e}^{x} \sin \left (x \right ) \]

19619

\[ {}\left (x \sin \left (x \right )+\cos \left (x \right )\right ) y^{\prime \prime }-x \cos \left (x \right ) y^{\prime }+y \cos \left (x \right ) = 0 \]

19620

\[ {}y^{\prime \prime }+\left (1+\frac {2 \cot \left (x \right )}{x}-\frac {2}{x^{2}}\right ) y = x \cos \left (x \right ) \]

19621

\[ {}x^{2} y^{\prime \prime }-2 \left (x^{2}+x \right ) y^{\prime }+\left (x^{2}+2 x +2\right ) y = 0 \]

19622

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

19623

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{x^{{1}/{3}}}+\left (\frac {1}{4 x^{{2}/{3}}}-\frac {1}{6 x^{{4}/{3}}}-\frac {6}{x^{2}}\right ) y = 0 \]

19624

\[ {}y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime }+y = 0 \]

19625

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-1\right ) y = -3 \,{\mathrm e}^{x^{2}} \sin \left (2 x \right ) \]

19626

\[ {}y^{\prime \prime }-\left (8 \,{\mathrm e}^{2 x}+2\right ) y^{\prime }+4 \,{\mathrm e}^{4 x} y = {\mathrm e}^{6 x} \]

19627

\[ {}y^{\prime \prime }+\cot \left (x \right ) y^{\prime }+\frac {\csc \left (x \right )^{2} y}{2} = 0 \]

19628

\[ {}x^{6} y^{\prime \prime }+3 x^{5} y^{\prime }+a^{2} y = \frac {1}{x^{2}} \]

19629

\[ {}x y^{\prime \prime }-y^{\prime }-4 x^{3} y = 8 x^{3} \sin \left (x^{2}\right ) \]

19630

\[ {}y^{\prime \prime } \cos \left (x \right )+\sin \left (x \right ) y^{\prime }-2 y \cos \left (x \right )^{3} = 2 \cos \left (x \right )^{5} \]

19631

\[ {}\left (1+x \right )^{2} y^{\prime \prime }+\left (1+x \right ) y^{\prime }+y = 4 \cos \left (\ln \left (1+x \right )\right ) \]

19632

\[ {}x y^{\prime \prime }+\left (x -1\right ) y^{\prime }-y = x^{2} \]

19633

\[ {}3 x^{2} y^{\prime \prime }+\left (-6 x^{2}+6 x +2\right ) y^{\prime }-4 y = 0 \]

19634

\[ {}y^{\prime \prime }+a^{2} y = \sec \left (a x \right ) \]

19635

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-y = {\mathrm e}^{x} x^{2} \]

19636

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+2 \left (1+x \right ) y = x^{3} \]

19637

\[ {}y^{\prime \prime }+\left (1-\cot \left (x \right )\right ) y^{\prime }-y \cot \left (x \right ) = \sin \left (x \right )^{2} \]